Evaluation of breast mass excision by 810 nm diode laser - Mahmood, Ali S. (Iraqi Journal of Laser, 2007)
Breast mass is by far the most important clinical problem that concerns the breast today. This study was carried out to evaluate diode laser as a cutting tool in breast mass excision and as a hemostatic tool for coagulation during surgery. Using 810 nm diode laser with optical fiber 600μm in diameter of conical tip, udder (cow's breast) tissue, and three female patients (mean age of 35.5 y with clinically palpable breast mass) had been used in this study. The patients were followed up regularly postoperatively. In preliminary work on udder tissue, the power needed for cutting and excision was 15W (power density= 5.3 kW/cm2). The time consumed for excision of a piece of udder tissue, 40×10×3 mm in dimensions was 5 min. The depth range of cutting was 2-3 mm. The speed of cutting was 0.6 cm/s. In the clinical work, the power needed for excision was 15 W (5.3 kW/cm2 power density). Power used for coagulation was ranging between 10-15W depending on diameter of blood vessel, the overall blood loss during surgery and postoperatively appeared to be less than that in conventional method. The contact laser scalpel produced clear appearance of surgical margin and saved dissection. Hemostatic capability assured clear anatomical visualization and few ligatures. No clinical evidence of infection at the wound site postoperatively. The results showed that the diode laser is effective in minimizing the intra-operative blood loss, postoperative blood loss, and effective in reducing the postoperative pain, swelling and edema. On follow up the patients were presented with relatively better healing progress, no wound infections, and no need for strong pain killer postoperatively.